Biomechanical and metabolic effects of a leaf spring structured midsole in heel-toe running - Wunsch. T.; Kröll, J.; Strutzenberger, G.; Schwameder, H. (Footwear Science, 2015)
Purpose: The purpose of this study was to investigate effects of a novel leaf spring midsole construction on biomechanical variables affecting running economy. The midsole construction is designed to exploit the directionality of the ground reaction force to shift the shoe anteriorly during the stance phase in running.Methods: Nine male long-distance runners ran 5 min on a treadmill (3 m s-1) with two types of shoes: a leaf spring structured midsole shoe and a standard reference shoe with a standard ethylene vinyl acetate foam midsole. Runner and shoe kinematics were analysed using a three-dimensional motion capture system, and oxygen cost was measured by an open circuit breath-by-breath spirometer. Group differences for all variables were tested using paired t-tests (p Results: The leaf spring structured midsole shoe significantly increased the anterior shift of the foot by 8 ± 4 mm (p = 0.001) during stance leading to an increased stride length (1%; p = 0.044), while oxygen cost (2%; p = 0.031) and stride rate (1%; p = 0.039) were significantly reduced compared to the reference shoe. Conclusion: It is concluded that the leaf spring structured midsole contributes to a more economic running style in heel-toe running at moderate running speeds.